The Effect of Psychoeducation with Roleplay on Knowledge of Physical Violence and Bullying Prevention in Adolescents in Junior High School - Sukmawati, Martini Nur; Sitanggang, Yohana Agustina; Lani, Tiara; Raziansyah, Raziansyah (STIKep PPNI Jawa Barat, 2024)
Aims: Bullying, characterized by physical or mental harm, can lead to negative effects on victims and perpetrators. Enhancing knowledge about bullying through role-play psychoeducation is crucial for prevention among junior high school students. Methods: This study uses a pretest-posttest design to investigate the impact of psychoeducation roleplay on bullying knowledge among junior high school students, finding a significant effect on learning outcomes. Results: Psychoeducation using roleplay can increase knowledge about bullying prevention among junior high school students at SMP Negeri 1 Karang Intan. This approach helps students understand the impact of bullying and how to prevent it, making them more enthusiastic and happy to participate. Research shows that increased empathy from witnesses can reduce bullying behavior. The relaxed and enjoyable environment of roleplay can help students understand the importance of prevention and reduce bullying. Conclusions: The roleplay method in psychoeducation significantly enhanced students' knowledge of bullying prevention among junior high school students in Negeri 1 Karang Intan, Banjar Regency.